2009
DOI: 10.1148/radiol.2511080590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Whole-Body CT Screening on the Cost-effectiveness of CT Colonography

Abstract: The addition of chest CT to CT colonography does not appear to be a cost-effective alternative. Further research is needed before whole-body CT can be recommended in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Further prospectively designed studies should clarify: If omission of oral contrast reduces the FDG uptake in the normal colonic wall and its excretion into stool (direct or via dissociation of FDG-loaded mucosa cells) [63],If the cut-off is dependent on the scanner type and requires a cross-calibration between different scanners [64],If an intrinsic normalisation to the mean SUV of the liver improves the accuracy of the cut-off [65], andIf low dose, non-enhanced PET/CT is more cost-effective than CT in identifying (detecting and classifying) relevant extra-colonic pathological features [66]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further prospectively designed studies should clarify: If omission of oral contrast reduces the FDG uptake in the normal colonic wall and its excretion into stool (direct or via dissociation of FDG-loaded mucosa cells) [63],If the cut-off is dependent on the scanner type and requires a cross-calibration between different scanners [64],If an intrinsic normalisation to the mean SUV of the liver improves the accuracy of the cut-off [65], andIf low dose, non-enhanced PET/CT is more cost-effective than CT in identifying (detecting and classifying) relevant extra-colonic pathological features [66]. …”
Section: Discussionmentioning
confidence: 99%
“…If low dose, non-enhanced PET/CT is more cost-effective than CT in identifying (detecting and classifying) relevant extra-colonic pathological features [66]. …”
Section: Discussionmentioning
confidence: 99%
“…any study, but it had an ICER below $22,000/ LYG. Virtual colonoscopy every 10 years dominated no screening in 1 study, 9 and the data from the rest of the studies reported an ICER below $23,000/LYG. Stool DNA testing every 3 years or 5 years did not dominate a no-screening strategy in any study, but these 2 strategies had an ICER below $35,000/LYG.…”
Section: Cost Effectiveness Of Current Screening Strategies Vs No Scrmentioning
confidence: 95%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] If a study used more than 1 model, then an additional entry was made in Table 1 for the given study. Table 2 provides further details, particularly on the sensitivity and specificity rates, costs for tests, and the types of sensitivity analyses performed.…”
Section: Identification Of Cost-effectiveness Analysesmentioning
confidence: 99%
See 1 more Smart Citation